Video-guided range of motion for functional recovery in non-hemorrhagic stroke: A literature review - Megayanti, Sri Dewi; Megawati, Putu Vera; Deani, Ni Wayan; Kusuma, I Made Jaya; Apriani, Ni Luh Putu Yudi (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Non-hemorrhagic stroke is a major cause of long-term disability, often resulting in motor impairment, reduced muscle strength, limited range of motion, and decreased independence in activities of daily living. Consistent and accessible rehabilitation strategies are therefore needed, especially during the transition from hospital to home care. Video-guided range of motion has emerged as a nursing-led approach to support home-based rehabilitation. Purpose: To describe the application of Evidence-Based Nursing through video-guided range of motion as an independent nursing intervention to improve functional recovery in patients with non-hemorrhagic stroke. Method: An Evidence-Based Nursing approach was conducted using the PICO framework. Literature searching was performed through PubMed, ScienceDirect, ProQuest, and Google Scholar. A total of nine relevant studies were critically appraised, including randomized controlled trials, feasibility studies, and comparative studies related to video-guided range of motion interventions in patients with non-hemorrhagic stroke. Results: The evidence indicated that video-guided range of motion improved exercise adherence, motor function, mobility, balance, and functional independence. Improvements were reported using validated outcome measures, including the Berg Balance Scale, Motor Functional Scores, and the Modified Barthel Index. Video-based range of motion showed effectiveness comparable to conventional face-to-face rehabilitation without increasing adverse events. Conclusion: Video-guided range of motion is a feasible and effective Evidence-Based Nursing intervention to support functional recovery and strengthen nursing practice in patients with non-hemorrhagic stroke, particularly in community and home-care settings.